Antisynthetase Syndrome in a Patient with Pulmonary Embolism and Nonbacterial Thrombotic Endocarditis - Vege, Anusha; Beery, Jesse; Kara, Areeba (Case Reports in Rheumatology, 2023)
Antisynthetase syndrome is a rare autoimmune disease within the subset of idiopathic inflammatory myopathies. The diagnostic criteria include the presence of an aminoacyl-tRNA synthetase antibody, and typical clinical findings, including myositis, mechanic’s hands, Raynaud phenomenon, unexplained fever, and interstitial lung disease. We describe a case of a 59-year-old male who presented with a 1-month history of progressive purplish discoloration and pain of the fingertips, dyspnea, cough, weight loss, fatigue, and who developed progressive proximal muscle weakness and dysphagia. Investigations revealed pulmonic valve and mitral valve marantic endocarditis, pulmonary embolism, myositis, organizing pneumonia, and elevation of anti-OJ antibodies. He was diagnosed with antisynthetase syndrome and treated with high dose corticosteroids and mycophenolate mofetil with a fair response.